Forced Marriage: The Authority of Custom Law in The Practice of Marriage In Kerinci, Jambi - Mega Puspita; Abdul Wahab Naf'an (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
This study discusses the authority of customary law in the practice of forced marriage in the community of Lekuk Limapuluh Tumbu Lempur, Kerinci, Jambi. Forced marriages were carried out against men and women who went out together and only returned after 20.00. They have to get married, even though they are not willing to do so, they are not even asked to be willing at all. This study uses a qualitative descriptive method. Data collection is done by observation, interviews, and documentation. This study shows that the decision to implement forced marriages was issued by four elements holding customary authority, namely the depati, ninik mamak, alim ulama, and cerdik pandai. This punishment is enforced in order to maintain religious rules, because a man and a woman who travel together until late at night have the potential to commit various violations of religious norms, especially adultery. The application of the forced marriage rule is intended as a preventive measure against these violations. Here the role of adat is to make forced marriage as a customary punishment intended to maintain religious norms.